(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
As part of an Action Research project, this research aims to investigate how students see the flipped classroom (FC) method of instruction, in which traditional classroom instruction takes a back seat to students’ independent study outside of class. In order to do this, a 13-week curriculum was devised to include multimedia technologies into writing courses for pupils. Information was gathered via a final survey, students’ ongoing self-reflections, and teachers’ field notes based on observations. The researchers set out to determine if and how flipped classrooms would improve students’ grasp of social science in upper-level secondary education. The efficacy was determined by the use of the experimental research approach. An experimental investigation using a pre- and post-test comparable group design was conducted. There was a random selection of sixty students from the History III group.